Analysis of Education and Training in Increasing Employee Productivity at PT Bima Golden Powerindo Medan - Marbun, Sondang Ni Bulan; Purba, Alimin; Ria, Chainar Elli; Fauzan K, Khairil; Afnina, Afnina (Journal Of Accounting Management Business And International Research, 2023)
This study examines the increase in employee productivity at PT Bima Golden Powerindo Medan through education and training. The problem in this study is that everyone has their own abilities that are not necessarily in accordance with the specifications needed by the company, so it is important to carry out education and training for employees. The research used qualitative research techniques. In data analysis using descriptive analysis methods, where the data that has been obtained is then described by the researcher in detail. The findings of this study that education and training can clearly increase employee work productivity. Thus, it can be suggested that the implementation of education and training for employees should be carried out as often as possible, supervised by the leadership, and reward workers whose productivity increases due to attending education and training.